PROFILE OF STATE TOBACCO LAWS. (Tufts Archival Research Center, 2007)
Tobacco Institute report profiling state tobacco laws. Summarizes state sales restrictions, minor laws, sampling and advertising restrictions, smoking restrictions, and taxations. Contains profiles on states with employment discrimination and ASHRAE standards.